Analysis of the Urgency of Material and Main Aspects of the Essential Concept of Natural Science in Kurikulum Merdeka - Sapitri, Riska Dia; Susanti, Dian (Jurnal Pijar Mipa, 2025)
Understanding the urgency of the material and the main aspects of the essential concepts of science is very important in learning. This study aims to analyse the urgency of the material and the main aspects of the essential concept in learning Natural Sciences (IPA) in the Independent Curriculum at the junior high school level. The Independent Curriculum provides flexibility for educators in designing contextual learning that is relevant to the needs of students, so that the selection of essential materials becomes very crucial. This study uses quantitative descriptive analysis with a simple random sampling technique on science teachers in Mataram City. Data was collected through a Likert-scale questionnaire to measure the level of urgency of science materials and the essentiality of aspects of the learning process. The results showed that most of the science materials, such as "Substances and Their Changes", "Life Organization Systems", and "Energy and Its Changes" were categorized as very urgent, with an average score of 3.44. In addition, aspects of the science learning process, such as "science-based problem solving", "science project development", and "science literacy skills", were also considered very essential, with an average score of 3.40. However, there are two materials with a moderate level of urgency, namely "Electricity and Magnetism" and "Human Reproductive System". Meanwhile, only one aspect of learning is considered essential (not very essential), namely "application of science in everyday life". This finding indicates the importance of adjusting the curriculum and learning strategies to ensure optimal achievement of competencies. Recommendations are directed to curriculum developers and educators to focus on materials and aspects of learning that best support students' scientific literacy and 21st-century skills.